Salvage open partial horizontal laryngectomy after failed radiotherapy: A multicentric study. (2nd May 2019) - Bertolin, Andy; Lionello, Marco; Ghizzo, Marco; Cena, Isida; Leone, Federico; Valerini, Sara; Mattioli, Francesco; Crosetti, Erika; Presutti, Livio; Succo, Giovanni; Rizzotto, Giuseppe
Abstract : Objectives: The primary aim of the present study was to report our multi‐institutional experience in surgical salvage with open partial horizontal laryngectomies (OPHL) after failed radiotherapy (RT) for laryngeal squamous cell carcinoma (LSCC). Secondary aims were to analyze the prognostic meaning of the main clinical and pathological parameters in relation to the oncologic outcome and to compare our results with the available literature. Study Design: A retrospective multicenter analysis of surgical oncological outcomes. Methods: We retrospectively review the clinical charts of 70 recurrent LSCC patients after primary RT failure undergone salvage OPHL. Results: At last follow‐up, 46 patients (65%) were disease‐free; six (9%) were alive with disease; nine (12%) died because of the disease; and nine (12%) died without evidence of disease. The final local control, overall survival, disease‐specific survival, and laryngectomy‐free survival were 87%, 75%, 87%, and 91%, respectively. Twelve patients (17%) experienced postoperative complications, whereas 18 patients (25%) experienced late sequelae. In five patients (7%), decannulation was not possible because of postoperative laryngeal stenosis. Conclusion: In selected patients, when proper selection criteria for conservation laryngeal surgery are adopted, OPHL can be considered for salvage after RT failure. Level of Evidence: 4 Laryngoscope, 130:431–436, 2020